Causality as a conceptual frame for forest policy analysis. - Tikkanen, Ilpo (Silva Fennica, 1981)
The need for the planning and analysing of public policy has increased in economic and social policy, along with the expansion of the public sector, i.e. as the number of aims of the policy has increased and the objects of it have become more versatile, the objects of allocation have likewise been multiplied. In addition, the significance of planning a public forest policy has been emphasized by many economic and social changes in forestry and the timber economy. The purpose of the present paper is to outline a general frame of reference for empirical policy analysis, upon which the effectiveness analysis of forest policy is also based. The approach serves as a methodological frame for the empirical analysis, presented in the following paper of this issue of Silva Fennica, in which econometric methods are applied to the examination of the effect of public forest policy.